The Asian financial crisis and policy response in the Philippines - Alburo, Florian A. (Philippine Review of Economics and Business (formerly The Philippine Review of Business and Economics), 1998)
Both in-country and regional evidence show that the Philippines did have the symptoms of the "Asian flu" before its outbreak into a full-blown Asian financial crisis. Although it cannot be validated (in a counterfactual sense), one can argue that it may have been the early start of the crisis elsewhere that now makes the country face less harsh consequences and adjustment. The Philippines is therefore not just an innocent bystander in the confluence of events in the region. This conclusion does not diminish the task of defining policies to address the root causes of the crisis and to adjust to the environment it creates. In terms of policy response, it may have been a blessing in disguise that the country did not have sufficient reserves to put up a defense early on. It is this which paved the way for the actual policy of freeing the exchange rate, rather than a conviction that the exchange rate should not be a target. Indeed, there are policies which are vestiges of this defense mechanism still in the books (e.g., interest rate cure). On the other hand, there remains a policy vacuum in the area of financial sector reforms, the very area that appears to be where the crisis started in the Asian region.